Pertanggungjawaban Direksi Perseroan Terbatas Terhadap Kebijakan Bisnis yang Menguntungkan di Luar Maksud dan Tujuan Perseroan Terbatas - Aryuanda, Alifrian Fajri (LPPM Universitas Ekasakti Padang, 2023)
A Limited Liability Company is a legal entity whose capital consists of shares, and the liability of its shareholders is limited according to the number of shares they own. Limited Liability Company has organs with specific functions and authorities. The Board of Directors of a Limited Liability Company is one of these organs, responsible for managing the company with good faith and full responsibility. This journal discusses the implementation of policies or decisions by directors that benefit the Limited Liability Company but are beyond its intended purpose, aiming to educate the public and business practitioners about the application of directorial policies or decisions in line with the objectives of the Limited Liability Company.